The effect of core stability training on the balance ability of young male basketball players - Gong, Jian; Gao, Huiyan; Sui, Jinghao; Qi, Fei (Frontiers in Physiology, 2024)
This study primarily analyzed the effect of Core Stability Training (CST) versus Traditional Strength Training (TST) respectively for 10 weeks on the balance abilities of adolescent male basketball players. subjects (age: 15.70±0.75, height: 178.4±8.31, weight: 66.55±8.34) were randomly assigned to either the Core Stability Training group or the Traditional Strength Training group. Three balance assessment indicators were selected: Single-leg Standing with Eyes Closed Test, Star Excursion Balance Test, and core endurance test in four directions. The results are as follows:(1)The scores were significantly different in both groups before and after the Single-leg Standing with Eyes Closed Test; (p < 0.01, d = 1.692, d = 1.837);(2)In the Star Excursion Balance Test, the scores of the experimental group showed significant difference(p<0.05) or highly significant difference (p<0.01) with an average effect size of (d=1.727) when the left or right foot supported in the other directions before and after the training. However, there was no significant difference in scores in the c direction when the left foot supported (p > 0.05, d= 0.954). (3) In the Core Four-Direction Endurance Test, there were no significant differences in scores for the control group before and after training (p > 0.05, d = 0.567), while the experimental group showed significant differences in scores before and after training (p < 0.05, d= 1.889). Both CST and TST can enhance the balance abilities of adolescent basketball players. CST improves dynamic balance and agility in multiple planes. In strength training, basketball coaches can incorporate CST training programs into their training plans.